CONGENITAL SYPHILIS EVALUATED FOR SYPHILITIC HEPATITIS - CASE SERIES - Dantas Lopes, Izailza Matos; Dantas Lopes, Gabriel; Calazans Batista, Jefferson Felipe; Santos Silva, José Rodrigo; Prado Reis, Francisco; Oliveira Lima, Sonia (Interfaces Científicas - Saúde e Ambiente, 2023)
Objective: To report case series evaluated for congenital syphilitic hepatitis. Method: Study conducted at Maternity Santa Isabel from December 2021 to May 2022. We evaluated newborns with congenital syphilis using data taken from the pregnant woman’s card, the child’s card, the anamnesis and exams performed in the follow-up consultations of these families. Complete medical records of infants who presented the criteria for the diagnosis of congenital syphilis of the Ministry of Health and the Center for Disease Transmission Control were included. Results: The review was 15 of which were selected that fit all the inclusion criteria. The babies were born with good vitality, term, one had low birth weight, six hepatomegaly, all treated with penicillin, nine had altered liver biochemical tests. At ultrasonography, Doppler was normal for all, one case of hepatosplenomegaly and one with splenomegaly. Two mothers who were diagnosed at the time of delivery had fewer than six consultations, their babies had neurosyphilis and presented developmental alertness. The child who had microcephaly and low birth weight also presented altered neurodevelopment. Of the pregnant women, three were over 30 years old, one was white, five had studied less than 8 years, thirteen were not working, family income of 1 minimum wage or less in twelve families. Eight were inadequately treated. Of the parents, eleven had studied less than 8 years and eleven were inadequately treated. Conclusion: The children with syphilis were born vigorous and had adequate treatment. Nine had altered hepatic biochemical exams, two had ultrasonographic alterations, however, without alterations in the Doppler. The children of untreated mothers had neurosyphilis and neurodevelopmental changes.